Level of Adoption of Innovation in Terrarium Cultivation among the Zoomer Generation - Andi Lelanovita Sardianti; muhamad yazid bustomi; pandhu rochman suosa putra; Rossy Mirasari; sri marlendi (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
The increasingly rapid development of technology provides changes in several aspects. Technological advances in this era apart from providing many benefits also provide challenges. One project that can accommodate the zoomer generation in following technological developments is the use of terrarium cultivation. Terrariums fulfill the 3 R principles, namely Reduce, Reuse, Recycle. By planting a terrarium, it means saving water, saving land, and reducing air pollution (Reduce), also reusing unused containers such as used jars (Reuse), and using animal waste as compost (Recycle). The facts in the field are that students as the zoomer generation have received training and socialization on terrarium cultivation, but the level of adoption (acceptance) of students regarding socialization and training on terrarium cultivation varies, therefore a study was carried out to what extent the level of adoption of the results of training and socialization in the application of cultivation terrarium for the zoomer generation. The data collection method used was a survey method with research subjects of the zoomer generation, namely 54 active students. The data collected is categorized tabulatedly and then analyzed descriptively qualitatively. This data analysis uses measurements of observation indicators using a